Evaluación de la viabilidad y sostenibilidad de la agricultura periurbana de bajo carbono como estrategia para la seguridad alimentaria y mitigación del cambio climático en la parroquia Juan Montalvo del cantón Latacunga - Calderón Moreno, Jeison Daniel (2024)
The research was developed in the peri-urban area from Juan Montalvo Parish, with the aim by assessing the viability and low-carbon agriculture systems sustainability. For this, it was made a survey in the KoBoToolbox software with a total 19 questions, in order to know people's perception about climate change, then, it was made the carbon footprint analysis with the Climate Hero software, which multiplies the consumption data (activity) by its corresponding emission factor, further, it was represented the got information, through statistical graphs generated in Excel based on the each neighborhood demographic variable, which makes up the peri-urban area and finally, based on a bibliographic query, it was contrasted the viability a sustainable agricultural system. As a result, it was determined, what 64% the inhabitants from peri-urban area parish, they are agree, which the population is not sufficiently informed about climate change and environmental problems. On the other hand, it is observed, what people 83% produce between (2-10) t CO2e annually, it is identified, which both corn and some legumes improve soil health allowing greater carbon absorption by the biomass, reaching 149.70 t/ha of CO2e, captured from annually. Finally, the environmental knowledge study, carbon footprint and low carbon agricultural system shows, which residents lack information and training that includes them as the research projects central focus and thus, achieving a continuous transition to sustainable agriculture and environmental sustainability.